Potencialidades e limitações da computação em nuvem: estudo de caso com ênfase ambiental - Wang, Rodrigo Daron (2012)
The computer is now a basic tool and its use is increasing due to new technologies coupled with the large-scaleproduction, whichreduces equipmentcost. But along with this technological advancement, there areproblems such as waste generation and energy consumption whichusually comes from non-renewable sources that generategreenhouse gases. This researchwas done at a universitybyanalyzingits computerssystems, and presentingCloudComputing, which is premised on the use of memory and processing capabilities of a server connected to the Internet,as an alternative to the current computing concept.This allows the clientcomputer to have a configuration with lower processing frequency and less storage memory, in theory, usingless energy and generating less pollution. The project builds,from the data of the university, a proposal using cloudcomputing with possible scenarios for its implementation. The proposal also takes into account the hardware and softwareof the computer, and environmental gains on lower energy consumption and reducedelectronic waste, resulting from a comparison between the systems of cloud computing and conventional.The acceptance ofthe facultywasobtained in a survey with questionnaires assessing an application that simulates a cloud system.Using questionnaires about the use of the new system it was possible to analyze the main problems. Three scenarioswere considered, with a life span of 8 years,for implementationof cloud computing in different percentages in the number of computers placedin terms of years. Those scenarios were compared against a controlled scenario using the current concept. With the scenarios was made an analysisof energy consumption, the mass of discarded computers, the cost of implementation and acceptability of the scenarios by users. A reduction of up to 62% on energy consumption and reductions up to 80% fromthe mass of discarded computerswere obtained, both using cloud computing. But with the larger number of computers addedusing the new concept, the greater the difficulties faced by users. Therefore it was considered that the best scenario was the one with a slower deployment, allowing more time to adapt to thenewsystem. However, the medium scenario was also considered as an option that should bring somedifficulty, but can still be deployed, bringing even greater environmental benefits.